THE ONLINE LEARNING AND STUDENTS’ MOTIVATION IN LEARNING ENGLISH: A CASE STUDY AT SMAN 1 DOMPU IN ACADEMIC YEAR 2020/2021 - Nurhairati Nurhairati; Lalu Thohir; Arafiq Arafiq (Program Studi Pendidikan Bahasa Inggris, 2021)
This study aimed at finding out the students’ perceptions about online learning. It focused on evaluating the process of online learning and the types of teaching models used by the teacher to attract students' attention in English online learning. The design of this study was qualitative. It was conducted on the second-grade students of SMAN 1 Dompu with a population of 350 students. From this number, 40 students were randomly taken as the sample. The data were collected through questionnaires and interviews. The result of the study reveals that the majority of students (73.5%) 29 out of 40 students perceived online learning as something good. They agreed that online learning can improve their motivations in learning English as online learning attract students' attention is relevant to the students' needs, build the students’ confidence, and fulfill their satisfaction. From all the online teaching models applied in the online classroom, the students preferred Problem Based Learning. Collaborative Language Learning would be more favorable as it could make the students learn together on-site in a group rather than to discuss material online. Meanwhile, Task-Based Learning was less favorable to the students as it might put them into a psychological burden during the pandemic period.